Leadership in education, corrections and law enforcement a commitment to ethics, equity and excellence - Normore, Anthony H.; Fitch, Brian D. (Bingley, U.K. : Emerald, 2011)
This volume fills a unique gap in the knowledge base the juncture between leadership, ethics, law, and how public institutions/organizations understand and practice the essence of all three. Authors from law enforcement, corrections education, and educational leadership present different yet overlapping constructs around ethics and law, and make an important step towards reconciling these differing views to demonstrate the significance of collaboration and partnerships for a common purpose. The volume develops a coherent theory on how multiple organizations can collaborate to gain 'public trust' for the 'greater good' of communities and society at large from the perspectives of law and ethics. Providing a broad-based view of the intersection where law and ethics meet leadership in multiple professions it sets the stage for the discussion of significance and timeliness of ethical behaviors and practices towards solving long lasting issues in education, corrections and law enforcement organizations. Implications for policy and practice are examined as well as creating an environment where the future discourse and direction of ethics and law in multiple organizations are discussed.
Introduction / Anthony H. Normore, Brian D. Fitch -- ch. 1. Understanding the ethical failures of law enforcement / Brian D. Fitch -- ch. 2. I am second : ethical leadership and self-denial / David C. Massey -- ch. 3. Ethical issues in school search and seizure / Lawrence F. Rossow, Jacqueline A. Stefkovich -- ch. 4. Ethical issues for a police psychologist / Dennis L. Conroy -- ch. 5. Responsible action as a construct for ethical leadership : investigating the effect of school and community on police involvement in student disciplinary affairs / Mario S. Torres, Nicole Poenitzsch, Jeffrey Burke -- ch. 6. The challenges of school-police partnerships in large urban school systems : an analysis of New York City's impact schools initiative / Kevin P. Brady -- ch. 7. Institutional moral architecture : from schools to prisons / Paul A. Wagner -- ch. 8. In pursuit of equity and excellence in law enforcement leadership / Alexandro Villanueva -- ch. 9. Theories of criminal justice : the influence of value attributions on correctional education / Brian D. Fitch, Anthony H. Normore, David R. Werner -- ch. 10. The value struggle between the families of law enforcement : the family at home and the family at work / Katarina A. Thomas -- ch. 11. Discrimination under section 504 and the Americans with Disabilities Act / Allan G. Osborne, Charles J. Russo -- ch. 12. Youth detention facilities and restorative justice : lesson for public education / Hollie J. Mackey.
Includes index.
Keywords: Education -- Leadership; Law -- Ethics & Professional Responsibility; Education -- Administration -- General; Education & the law; Law & society; Educational leadership; Leadership -- Moral and ethical aspects; Legal ethics